Occupational therapy with elders : strategies for the COTA - Helene Lohman; Sue Byers-Connon; René L. Padilla (St. Louis Missouri : Elsevier, 2019)
"Occupational Therapy with Elders: Strategies for the COTA, 4th Edition is the only comprehensive book on geriatric occupational therapy designed specifically for the certified occupational therapy assistant. It provides in-depth coverage of each aspect of geriatric practice -- from wellness and prevention to death and dying"-- Publisher's description
Keywords: Aged; Rehabilitation; Occupational therapy for older people; Electronic books